Development of a collaborative chronic care model for management of cardiometabolic disease in low- and middle-income countries - Pamela Miloya Godia; Michelle Hadjiconstantinou; Rosa Weyula; Usagi Ememwa; Samuel Seidu; Peter Njoroge; Joyce Muhenge Olenja; George Nyadimo Agot; Jamin Avugwi; Mary Coleman; Alfred Yawson; Filipe Dulce; et al. (PLoS ONE, 2026)
Introduction Cardiometabolic diseases (CMD) which include cardiovascular disease (CVD), diabetes, hypertension, and other metabolic syndromes represent a significant global health burden. Three quarters of global CVD deaths occur in low-and-middle-income countries (LMICs) and CMD account for approximately 35 percent of deaths in the Sub-Saharan Africa (SSA) region. The COVID-19 Pandemic significantly accelerated the transformation of the landscape in the management of patients with multiple long-term conditions, prompting innovation in healthcare delivery and highlighting the importance of more integrated and adaptable healthcare approaches. Addressing CMD requires a multifaceted approach involving both individual-level interventions, health system approaches, community-based approaches, and broader population-wide strategies for prevention. Aim This study aimed to develop and pilot a person-centred model of health care for CMD management, integrating key principles from the Chronic Care Model (CCM) and Collaborative Care Model (CoCM) to assess feasibility and potential scalability in LMICs. Methods The development of the CREATE intervention took a mixed method approach utilizing both qualitative and quantitative methodologies, including a systematic review, qualitative synthesis, and needs assessment including the delivery of workshops with local stakeholders and people living with CMD in Ghana, Kenya and Mozambique. Results A CoCCM with the following components was developed as the CREATE intervention: 1) Self-Management support, 2) Decision support (which included health care provider training), 3) Community linkages, 4) Organisation of health care, 5) Clinical information system, and 6) Delivery system design (streamlining the referral pathway). The CREATE intervention was informed by a systematic review, needs assessment, and six stakeholder workshops across three LMICs, identifying barriers such as limited primary care infrastructure, lack of referral systems, and gaps in self-management education. Conclusion This is the first CoCCM model for Multiple Long-term Conditions (MLTC) to be developed for SSA. The intervention is currently being tested as part of a feasibility study in Kenya, Ghana and Mozambique. The CREATE intervention has the potential for adaptability to local context, however there is need for more rigorous research to evaluate the model effectiveness in relation to improving patient outcomes.